Genética de populações de Aegla longirostri (crustacea, decapoda, anomura) da região central do Rio Grande do Sul - Buchmann, Darine (2009)
The Aeglidae are Decapoda crustaceans endemic from the neotropical region of South America. They are the only anomuran family entirely restricted to freshwater, occurring mainly in streams. Requirement for well conserved habitat has restricted the populations to springs, as an effect of the constant degradation of continental aquatic ecosystems. In the central region of Rio Grande do Sul state, the species Aegla longirostri, besides suffering the effects of habitat fragmentation, is subjected to a mountainous geographic barrier, which has been separating the basins of River Guaíba and River Uruguay for about 11 my. Microsatellite loci are molecular markers with high levels of heterozigosity which have been widely used in population genetics studies. Microsatellite markers previously isolated from A. longirostri genome were characterized and the levels of heterozigosity and allelic diversity were calculated for each locus. A total of seven polymorphic microsatellite loci were used to verify genetic variability among four different populations from central region of Rio Grande do Sul state concerned the two basins described above. Results show a great genetic differentiation among all populations and not only between populations isolated by the geographic barrier. Factors as lack of larval stage and low dispersion capacity are possibly contributing to such differentiation level. Anthropic actions, resulting in alteration of aquatic environments, can also be a more recent factor contributing to the genetic diversity among the populations studied, since aeglids are very strict in relation to the water quality.